2021
DOI: 10.1021/acsami.1c07425
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of Polymers on Bioinspired Chemically Structured Substrates

Abstract: Natural biological surfaces exhibit interesting properties due to their inhomogeneous chemical and physical structure at the micro-and nanoscale. In the case of hair or skin, this also influences how waterborne macromolecules ingredients will adsorb and form cosmetically performing deposits (i.e., shampoos, cleansers, etc.). Here, we study the adsorption of hydrophilic flexible homopolymers on heterogeneous, chemically patterned substrates that represent the surface of the hair by employing coarse-grained mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…The shape of the damage patterns is qualitatively similar to that observed in previous AFM experiments at lower resolutions. 25,30,45 Similar coverage surface coverage projections are also observed for water and n-hexadecane (Fig. S3 in the ESI †).…”
Section: Monolayer Propertiessupporting
confidence: 73%
See 4 more Smart Citations
“…The shape of the damage patterns is qualitatively similar to that observed in previous AFM experiments at lower resolutions. 25,30,45 Similar coverage surface coverage projections are also observed for water and n-hexadecane (Fig. S3 in the ESI †).…”
Section: Monolayer Propertiessupporting
confidence: 73%
“…Random removal of lipid chains is likely from chemical treatments such as bleaching. Other authors have observed roughly circular 45 and striped 30 damage patterns on hair surfaces. However, the size of these regions is comparable to the size of the surfaces employed in our CG-MD simulations.…”
Section: Monolayer Propertiesmentioning
confidence: 86%
See 3 more Smart Citations